Optimization of Waiting Time for Coal Loading and Unloading Activities to Ships at PT Andhini Samudera Jaya Bunati Branch - Muhammad Syfaa Ussalam; Bagaskoro Bagaskoro; RR Retno Sawitri Wulandari (Greenation International Journal of Tourism and Management, 2023)
Coal is one of the fossil materials used as fuel for power generation. The miningindustry, especially coal in Indonesia, has an important role for the state, especially as a source of state revenue that is able to support the country's economic growth. One of the areas in Indonesia that is a coal-producing area is Laut Island, South Kalimantan. The results of coal mining in the South Kalimantan area are mostly exported abroad. The mode of transportation chosen as a means of transporting coal is a mode of sea transportation that can load large quantities of cargo. Coal loading activities can be carried out if the loading room (ship hatch), cargo (coal) and loading equipment (floating crane) are ready to carry out loading and unloading activities. After the ship docks at the loading point, the captain will send a NOR (Notice of Readiness) to all charter parties indicating that the ship is ready to carry out loading/unloading activities. However, the number of ships that come and will load coal with the amount of loading and unloading equipment available is not comparable. This causes waiting time, so that the implementation of loading coal to large ships is not effective because too much time is wasted. Over time, ship service providers are growing and competing to provide effective, efficient and satisfying services for service users. Both for domestic and foreign service users.